Abnormal regional homogeneity in patients with irritable bowel syndrome: A resting‐state functional MRI study. Issue 12 (25th September 2015) - Ke, J.; Qi, R.; Liu, C.; Xu, Q.; Wang, F.; Zhang, L.; Lu, G.
Abstract: Background: Task‐related brain imaging research has implicated abnormal central processing of visceral sensation in irritable bowel syndrome (IBS). However, how brain function of IBS patients is altered during resting‐state remains to be determined. We investigated spontaneous brain activity of patients with IBS using regional homogeneity (ReHo) analysis in resting‐state functional magnetic resonance imaging (rs‐fMRI). Methods: Thirty‐one patients with diarrhea‐predominant IBS and 32 age‐ and sex‐ matched healthy controls underwent clinical assessments and rs‐fMRI scanning. ReHo maps were acquired by calculating the Kendall's coefficient of concordance and compared between the IBS group and the control group. The effects of psychological disturbance on group differences were assessed by including anxiety and depression levels as covariates in the statistical analyses. Multiple regression analyses were conducted to examine the relationship between ReHo values and disease duration, symptom severity, and pain intensity. Key Results: Compared with controls, IBS patients showed increased ReHo in the postcentral gyrus and thalamus and decreased ReHo in the anterior cingulate cortex and prefrontal cortex. The inclusion of anxiety and depression as covariates did not alter ReHo differences between the two groups. Furthermore, significant correlations were found between clinical indices and ReHo values in some brain regions in the IBS group. Conclusions & Inferences: IBS patients have abnormal local synchronization of spontaneous brain activity in regions involved in visceral afferent processing, emotional arousal, and cognitive modulation. Combining rs‐fMRI and ReHo analysis seems to be a valuable approach to investigate the neural basis of IBS. Abstract : IBS patients have abnormal local synchronization of spontaneous brain activity in regions involved in visceral afferent processing, emotional arousal and cognitive modulation. Combining rs‐fMRI and ReHo analysis seems to be a valuable approach to investigate the neural basis of IBS.